2022
DOI: 10.3390/jfmk7040087
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Skeletal Muscle Oxygen Utilization

Abstract: The cardiovascular and skeletal muscle systems are intrinsically interconnected, sharing the goal of delivering oxygen to metabolically active tissue. Deficiencies within those systems that affect oxygen delivery to working tissues are a hallmark of advancing age. Oxygen delivery and utilization are reflected as muscle oxygen saturation (SmO2) and are assessed using near-infrared resonance spectroscopy (NIRS). SmO2 has been observed to be reduced by ~38% at rest, ~24% during submaximal exercise, and ~59% durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…This contradicts the majority of existent evidence, whereby associations between muscle mass and CRF have consistently been demonstrated in both healthy and clinical cohorts. 6,28,29 Given the role of skeletal muscle in oxygen utilization, 30 the mechanistic basis of this association is fairly clear. One potential explanation for the lack of relationship reported herein may be the method used to assess muscle size.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts the majority of existent evidence, whereby associations between muscle mass and CRF have consistently been demonstrated in both healthy and clinical cohorts. 6,28,29 Given the role of skeletal muscle in oxygen utilization, 30 the mechanistic basis of this association is fairly clear. One potential explanation for the lack of relationship reported herein may be the method used to assess muscle size.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations to reduce variability and errors in data collection, analysis and interpretation were also provided. Salvatore et al [ 5 ] summarized the effects of aging in healthy individuals and muscle O 2 utilization; aging reduces SmO 2 at rest, and during submaximal and maximal exercise, and extends the timeframe for restoration of SmO 2 following exercise. In 2021, Cornelis et al [ 6 ], summarizing the results of 11 clinical trials on the impact of exercise therapy on lower limb SmO 2 evaluated by NIRS in patients with lower-extremity artery disease, showed that exercise training improved the de-oxygenation and re-oxygenation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged and repetitive exposures to these risk factors may have biomechanical and physiological impacts such as restriction of the blood circulation to body parts and consequently reduction of supplied oxygen to the muscles [18]- [20]. Muscle and oxygen consumption in human skeletal muscles [21], [22]. This can lead to faster rate of fatigue, and prolonged physiological stresses may even lead to tissue damage and eventually musculoskeletal symptoms will start to emerge [23]- [25].…”
Section: Introductionmentioning
confidence: 99%